IMPLEMENTATION OF THE PROJECT-BASED LEARNING MODEL ASSISTED BY AUGMENTED REALITY MEDIA TO IMPROVE IPAS LEARNING OUTCOMES IN GRADE 5 ELEMENTARY STUDENTS - Wati, Sari Riski; Prihandono, Trapsilo; Soepeno, Bambang (MIDA : Jurnal Pendidikan Dasar Islam, 2025)
This study aims to improve the learning outcomes of Natural and Social Sciences (IPAS) subjects for fifth-grade elementary school students through the application of the Project Based Learning (PJBL) model assisted by Augmented Reality (AR) media. The background of this research is the low student achievement due to conventional teaching methods and the lack of visualization of concepts. This study used a Classroom Action Research (CAR) method consisting of two cycles with a total of 25 students as subjects. Data collection techniques included learning outcome tests, observations, and student project documentation. The results showed that the implementation of PJBL assisted by AR media can enhance student engagement and improve IPAS learning outcomes. The percentage of learning mastery increased from 64% in the first cycle to 88% in the second cycle. AR media proved to be effective in helping students visualize abstract concepts more clearly and attractively, as well as in supporting the development of 21st-century skills such as collaboration and communication.